Practical Reason, ‘Civil Prudence’ and the Law: Vico’s Epistemology and Economic Action - Solari, Stefano (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Adopting a single and credible model of man in both law and economics would help the study of an appropriate legal framing of markets. An appropriate common philosophical approach could avoid the incommensurabilities existing between the two disciplines. The paper rests on the hypothesis that Vico’s epistemology, based on a practical approach, is suitable to establish an original connection between economics and the law, assuming normative theoretical elements as relevant items in economic reasoning. The peculiar epistemology of Vico based on uncertainty is exposed and the specific model of man is discussed. It is shown how Vico’s is a systematic and coherent scientific programme based on a specific open-ended view of man and society. Vico introduced also a vision of what our society ought to be, some civilising value that can constitute a bridge between law and economics. Besides those of his friends Genovesi and Galiani, the political economy approach most compatible with Vico’s epistemology is Austrian economics, broadly intended. It shares a similar view of rationality and of the evolving order of society. However, it lacks a theorisation of collective awareness that was one of the major achievements of Vico. Keywords: Vico; Uncertainty; Civil life; Austrian economics; Collective awareness. Index: 1. Reconsidering homo-oeconomicus in a legal context – 2. The epistemology of Giovanbattista Vico – 3. Agency in Vico – 4. From agency to institutions – 5. The law and collective awareness – 6. The practical action of a prudent man – 7. Conclusion: Vico and Austrian economic theory – References